Les notices lexicales au service de l’apprentissage du FLE à l’aide des dictionnaires bilingues - Ucherek, Witold; Grabowska, Monika (2023)
In this study, we focus our attention on the lexical notes in Polish-French bilingual dictionaries which are supposed to provide additional information on the semantics of the items and, therefore, on their translation into the target language. After having identified three bilingual dictionaries containing such lexical notes (placed in boxes or frames within the structure of the book), we classify their content into 15 categories. More than half of them are based on semantic relations between lexical units, including false friends, onomasiological fields, and (para)synonyms. Fifty-five boxes out of 215 deal with formal relations, most often paronymy. The numerically least important group is made up of boxes containing different usage advice. We identify also some methodological errors in the conception of the boxes (mostly due to the irrelevance of the content for the target audience).
Keywords: bilingual dictionary; lexicography; lexical note; text boxes; learning French as a foreign language